Assessment of Municipal Waste Water of Duhok District and Its Usefulness for Irrigation - Dawud, Kurdistan I.; Abdi, Sarbast I.; Umer, Mustafa I. (CV. Literasi Indonesia, 2024)
Nowadays there is a water crisis, farmers usually use wastewater and well water for agricultural cultivation. A pot experiment was used to investigate the influence of Duhok municipal wastewater for irrigation of broccoli plants of the genus (Brassica oleracea var. Italica (Broccoli) as compared to fresh water on broccoli parts and morphology of the plant. Municipal wastewater can be a rich source of necessary nutrients for plant growth when used as irrigation water. In this investigation, the municipal wastewater was preserved in plastic bottles taken from sewage sludge called (Hishkero) river, while the utilized soil got around the Misuriké district under a loamy soil texture class. The result showed that the broccoli plant was significantly affected by wastewater compared to freshwater in increasing potassium, lead, and copper (1.92 ± 0.05 % ), (1.70 ± 0.05 %), (0.66 ± 0.02 mg/kg-1), (0.56 ± 0.02 mg/kg-1), (0.23 ± 0.03 mg/kg-1), (0.05 ± 0.03 mg/kg-1) respectively. While the broccoli plant for macro-nutrient accumulation (NPK) was significantly accumulated in shoot and head more than roots (1.45 ± 0.04 %), (1.41 ± 0.04 %), (0.24 ± 0.03 %), (0.33 ± 0.03 %), (2.17 ± 0.07 %), (2.11 ± 0.07 %) respectively. In conclusion, the nutrient content in broccoli was improved by wastewater as it has high nutrient contents with permissible levels of hazardous heavy metals of as lead and cadmium especially in the eaten part.